A rare case of metastatic small cell neuroendocrine carcinoma of the lung presenting as isolated thrombocytopenia - Adreana DeMarinis; Fahad Malik; Tommy Matin; Zalmi Rahmany; Tyler Putnam; Jay Nfonoyim (Journal of Community Hospital Internal Medicine Perspectives, 2019)
Small cell neuroendocrine carcinoma (SNEC) is a high grade and poorly differentiated neuroendocrine tumor which typically presents as a primary pulmonary neoplasm near the bronchial region. Due to the aggressive nature of the tumor, there are many ways it can initially present, mostly involving the lungs. We present a case of a 68-year-old male patient who initially presented with new-onset of severe thrombocytopenia with superimposed pneumonia. It was late in the progression of the disease that histopathology from the bone marrow confirmed SNEC, which presented only after it metastasized to the bone marrow by way of a rare paraneoplastic syndrome. Furthermore, the bone marrow biopsy revealed atypical markers not commonly seen in SNEC. Since this was such an atypical presentation of SNEC, management was limited to stabilization of the patient. The patient expired two weeks later.